A process evaluation of selected programs of the Department of Health (DOH): RPRH education and communication - Mary Pauline V. Saquing; Norliza M. Nordan (Philippine Institute for Development Studies (PIDS), 2021)
Seven years ago, the Responsible Parenthood and Reproductive Health Act was signed into law. Its revised implementing rules and regulations was issued in 2017 with its general provisions citing the guiding principles of its implementation, provision and financing of care, public awareness and education, governance, prohibited acts and penalties, and miscellaneous provisions. For the past years, Department of Health has taken the lead in the implementation of the RPRH law and has worked with other national agencies and civic society organizations to realize the objectives of the law. At the core of the mandate of the RPRH is the delivery of responsible parenthood and reproductive health services and information. Among the key provisions of the law are financing, governance, and public awareness and education. This paper discusses the extent of implementation of the RPRH education and communication, specifically on the output-level performance of the key implementing agencies and personnel, and the enabling factors and barriers that affect their implementation of the program. Results of the review of relevant documents, interviews, and FGDs show that the key agencies in the implementation of the RPRH education and communication manifest compliance with some of the provisions of the RPRH Law's IRR.
Keywords: 330; responsible parenthood and reproductive health; RPRH education; RPRH communication; comprehensive sexuality education